Atomistic simulation of Mg2SiO4 and Mg2GeO4 spinels: a new model - Wright, Kathleen; Gale, Julian; Blanchard, M. (Springer-Verlag GmbH, 2005)
We have developed a new interatomic potential model for the simulation of ringwoodite, the high-pressure phase of Mg2SiO4, and its low-pressure analogue, Mg2GeO4 spinel. The main novelty is the addition of a breathing shell model that enables us to accurately describe the structural and elastic parameters of both spinels up to 15PGs. Our model has also been applied to the two other Mg2SiO4 polymorphs in order to test its transferability. We find that although it is able to reproduce the structure and physical properties of wadsleyite, the breathing shell description is less successful with forsterite. the Mott-Littleton method has been used to calculate the energy of the intrinsic point defects in both spinels. The results indicate that these phases are likely to have the same defect population with teh MgO partial Schottky defect predominating.